Preliminary study of ectoparasite fauna on hirundo sp. at UiTM Kuala Pilah (Beting) / Fatin Nadia Azwa Zainal - Zainal, Fatin Nadia Azwa (Faculty of Applied Sciences, 2014)
The aim of the present study was to determine the ectoparasites species that infested Hirundo sp. of UiTM Kuala Pilah (Beting) besides to recognize the ectoparasites that has potential risk to human. In this study, five families of lice (Boopidae, Trichodectidae, Menoponidae, Laemobothriidae and Ricinidae) and one families of mite (Dermanyssidae) were recovered. In addition, the study of ectoparasites on Hirundo sp. also might deliver some knowledge and understanding about organisms which inhibit the skin or outgrowth of the skin of other organism for various periods, and may detrimental to the latter. Other than that, this study will help others to understand more on the distribution and host interactions of ectoparasites from avifauna in UiTM Negeri Sembilan, Kuala Pilah campus.